Optimization and Antioxidant Activity Test Of SMEDDS Bay Leaf with Palm Kernell Oil as Oil Phase - Fea Prihapsara (Universitas Sebelas Maret, 2017)
One of the plants which can produce antioxidants is the bay leaves (Syzygium polyanthum (Wight) Walp). Generally, extract have big size molecule and low solubility. To overcome low solubility of extract, it was formulated into self microemulsifying drug delivery system (SMEDDS) using oil Palm Kernel Oil (PKO) as a carrier oil. This research, aims to produce mikrometer-sized emulsion and thus can be used at low dose in SMEDDS mikroemulsion preparation. And this research was conducted to determine the antioxidant activity of SMEDDS bay leaf extract. Palm kernell oil is used because its suitable for SMEDDS and has medium chain trigliseride that can Increase drug transport through lymphatics thereby reducing first pass metabolism. Optimization of surfactant, cosurfactant and oil phase was determined with trial and error method. The results showed that the optimum SMEDDS formula was tween 80 : PEG 400 : Palm Kernell Oil (1,6 : 2,4 : 1) in 5 mL. SMEDDS extract of bay leaves had emulsification time 13.93 seconds, average of droplet size was 218,9 nm and polidisperse index 0,203. Morphological observation showed the mikroemulsion particles had spherical shaped. SMEDDS product of bay leaf extract has powerful antioxidant potential, the value of IC50 is 40,7177 ppm.